Shakespeare Studies in Colonial Bengal : the Early Phase. - Dahiya, Hema (Cambridge Scholars Publishing, 2013)
Shakespeare Studies in Colonial Bengal: The Early Phase represents an important direction in the area of historical research on the role of English education in India, particularly with regards to Shakespeare studies at the Hindu College, the first native college of European education in Calcutta, the capital city of British India during the nineteenth century. Focusing on the developments that led to the introduction of English education in India, Dr Dahiya's book highlights the pioneering r ...